MORFOLOGI, ANATOMI DAN UJI HISTOKIMIA RIMPANG Curcuma aeruginosa Roxb; Curcuma longa L. DAN Curcuma heyneana Valeton dan Zijp. - Trimanto, Trimanto; Dwiyanti, Dini; Indriyani, Serafinah (BERITA BIOLOGI, 2018)
Curcuma is a genus of family Zingiberaceae. Its rhizomes, as well as leaves, have long been used in the traditional medicine. This research aimed to examine the morphological and anatomical structure as well as the primary and secondary metabolites of Curcuma aeruginosa Roxb, Curcuma longa L, and Curcuma heyneana Valeton & Zijp. The Anatomical structure, histochemical test and secretory cell density were observed microscopically. The Histochemical test consisted of amilum, protein, lipid, tanin, alkaloid dan flavonoid tests. Observation of anatomical structures of the of rhizome showed that starch grains has a medium size and shape of starch was oval. Rhizomes of Curcuma longa and C. aeruginosa had a positive correlation for starch, protein, lipids, alkaloids, flavonoids and tannins. C. heyneana has the highest density value on protein while C. longa has the highest density value on lipids, alkaloids, flavonoids and tannins.